ROS1-positive non-small cell lung cancer: from genomics to treatment decisions - Wespiser, Mylène; Gille, Romane; Pérol, Maurice (Frontiers in Oncology, 2026)
ROS1 rearrangements define a distinct, targetable subset of non–small cell lung cancer (NSCLC), representing ~2% of non-squamous cases and frequently presenting with metastatic disease and CNS involvement. Multiple ROS1 tyrosine kinase inhibitors (TKIs)—from crizotinib to newer agents such as entrectinib, lorlatinib, repotrectinib, taletrectinib, and the highly selective zidesamtinib—have improved systemic and intracranial outcomes, although resistance remains inevitable and biologically diverse, involving both on-target kinase mutations and off-target mechanisms. This review synthesizes current knowledge on ROS1 biology, diagnostic strategies, therapeutic options, and resistance mechanisms. We outline ROS1 fusion architecture and signaling, highlight partner-specific features, and summarize available diagnostic modalities. In clinical practice, RNA-based next-generation sequencing (NGS), often preceded by immunohistochemistry screening, provides the most sensitive approach for fusion detection and resistance profiling. Given the expanding therapeutic landscape and increasing complexity of treatment sequencing, we adopt a pragmatic, practice-oriented framework. CNS-penetrant next-generation TKIs with activity against common resistance mutations now constitute preferred first-line therapy. Repotrectinib and taletrectinib show strong systemic and intracranial efficacy, including activity against ROS1 G2032R, whereas zidesamtinib offers high selectivity with encouraging early data. Pemetrexed-based chemotherapy remains an effective option, whereas immune checkpoint inhibitors provide limited benefit. At progression, molecular reassessment is essential to guide tailored therapy. Looking ahead, priorities include optimizing sequencing strategies, evaluating perioperative targeted approaches, and incorporating genomic monitoring to anticipate resistance. These advances are reshaping the natural history of ROS1-rearranged NSCLC and supporting a more durable, precision-driven treatment paradigm.